What will be when he grows up? Parents expectations of deaf kids - Bittencourt, Zélia Z. L. C.; Mendonça, Fernanda B.; Silva, Ivani Rodrigues (Medicina (Ribeirao Preto), 2011)
Study design: Qualitative and exploratory survey. Objective: This study aims to identify the expectations ofparents of deaf children about the development and their future, verify the socio-demographic characteristics of these parents and to verify how the communication between the deaf and their families is.Methods: To reach this aim, qualitative methodology was adopted using open-ended interviews havingas subject parents of deaf children who attend the rehabilitation program in Centro de Estudos e Pesquisasem Reabilitação "Prof Dr Gabriel O S Porto" CEPRE. The data were collect through questions focusingaspects like the knowledge of the deafness, the rehabilitation process, the communication with the deafchildren and the expectations about the future of their son. Results: The findings showed the expressiveparticipation of mothers in the rehabilitation process as the main speaker with the deaf son. The mostpart of the families had the perceptions of the deafness in the early years of the life of their sons, exceptin one case of late discovery because the child was assisted as having autism. The communication ofthe parents with the deaf son was realized through domestic signs and the main concern of the parentswere in their kids schooling and their learning difficulties, the lack of trained teachers and prejudice dueto communication trouble. Conclusion: The expectation of parents is marked by anxiety and uncertaintyabout the independence and autonomy of the deaf child. The parents were afraid about the future of thedeaf son expressing concern and insecurity with the public school inadequacy and the lack of government policies to support deaf people along their lives.